2022
DOI: 10.1155/2022/6389906
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Cross-Talk between Oral Squamous Cell Carcinoma and Type 2 Diabetes: The Potential Role of Immunity

Abstract: Background. This bioinformatics study was aimed at evaluating type 2 diabetes (T2D) and oral squamous cell carcinoma (OSCC) with regard to related immune cells and prognosis. Methods. We downloaded the data on OSCC from TCGA and for T2D from GEO database. Differentially expressed genes were analyzed, i.e., for OSCC genes with p   value < 0.01 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…23 For example, PSMC4 gene expression was found to be upregulated in a wide variety of human tumor tissues, including pituitary adenomas, oral squamous cell carcinoma, laryngeal cancer, breast cancer, and prostate cancer. [24][25][26][27][28] Not only that, PSMCs are considered to act as oncogenes and contribute to poor prognosis in multiple cancers. A previous study reported that PSMC1 promotes the proliferation and migration of lung adenocarcinoma cells and is related to poor prognosis in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…23 For example, PSMC4 gene expression was found to be upregulated in a wide variety of human tumor tissues, including pituitary adenomas, oral squamous cell carcinoma, laryngeal cancer, breast cancer, and prostate cancer. [24][25][26][27][28] Not only that, PSMCs are considered to act as oncogenes and contribute to poor prognosis in multiple cancers. A previous study reported that PSMC1 promotes the proliferation and migration of lung adenocarcinoma cells and is related to poor prognosis in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Genome editing or small-molecule mediated inhibition of DYRK2 significantly bypassed bortezomib resistance in both multiple myeloma and breast cancer cells ( 69 ). PSMC4 is also considered a biomarker in endometrial cancer ( 70–72 ), breast cancer ( 60 ), hepatocellular carcinoma ( 73 ), oral squamous cell carcinoma ( 74 ), and laryngeal carcinoma ( 75 ). Combined with our data in the present study, PSMC4 may be a novel biomarker and therapeutic target for drug-resistant cancer patients demonstrating high levels of PSMC4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…PSMC4 has been shown to be essential for the normal function of the proteasome in a variety of cellular processes, including DNA repair, cell cycle regulation and protein regulation. In addition, PSMC4 can also regulate the progression of multiple types of cancer, including breast cancer, 8 endometrial cancer, 9,10 PCa, 11 oral squamous cell carcinoma 12 . Studies have showed that high level of PSMC4 was positively correlated with shorter survival in breast cancer 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PSMC4 can also regulate the progression of multiple types of cancer, including breast cancer, 8 endometrial cancer, 9 , 10 PCa, 11 oral squamous cell carcinoma. 12 Studies have showed that high level of PSMC4 was positively correlated with shorter survival in breast cancer. 8 Moreover, PSMC4 can serve as one of the best reference genes for type 1 endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%